Approximation of the Summation-Integral-Type q-Szász-Mirakjan Operators - Mei-Ying Ren; Xiao-Ming Zeng (Abstract and Applied Analysis)
We introduce summation-integral-type q-Szász-Mirakjan operators and study approximation properties of these operators. We establish local approximation theorem. We give weighted approximation theorem. Also we estimate the rate of convergence of these operators for functions of polynomial growth on the interval [0,∞).